2015
DOI: 10.1001/jama.2015.6789
|View full text |Cite
|
Sign up to set email alerts
|

Female Hormonal Factors and the Risk of Endometrial Cancer in Lynch Syndrome

Abstract: IMPORTANCE Apart from hysterectomy, there is no consensus recommendation for reducing endometrial cancer risk for women with a mismatch repair gene mutation (Lynch syndrome).OBJECTIVE To investigate the association between hormonal factors and endometrial cancer risk in Lynch syndrome. DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort study included 1128 women with a mismatch repair gene mutation identified from the Colon Cancer Family Registry. Data were analyzed with a weighted cohort approach. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 42 publications
4
60
0
7
Order By: Relevance
“…No significant effect of contraceptive use on the ECC risk was detected among MLH1 mutation carriers in the study of Blokhuis et al (13), although that study included only 12 cases of EC in 87 mutation-positive females, in comparison with 121 mutation-negative female relatives. However, the previously described large retrospective cohort study revealed a marked EC risk reduction among LS mutation carriers with a history of contraceptive use extending to 1 year (19). The results of the present study, demonstrating fewer spontaneous and induced abortions among mutation carriers, may also be interpreted as more premeditated family planning being carried out for the LS mutation carriers tested at a fertile age, and this warrants further investigation.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…No significant effect of contraceptive use on the ECC risk was detected among MLH1 mutation carriers in the study of Blokhuis et al (13), although that study included only 12 cases of EC in 87 mutation-positive females, in comparison with 121 mutation-negative female relatives. However, the previously described large retrospective cohort study revealed a marked EC risk reduction among LS mutation carriers with a history of contraceptive use extending to 1 year (19). The results of the present study, demonstrating fewer spontaneous and induced abortions among mutation carriers, may also be interpreted as more premeditated family planning being carried out for the LS mutation carriers tested at a fertile age, and this warrants further investigation.…”
Section: Discussionsupporting
confidence: 58%
“…According to these studies, risk factors are partially shared in sporadic and hereditary EC, since the BMI appeared not to have an effect on EC risk, although parity, longer use of hormonal contraceptives and a later age at menarche reduced the risk of EC in LS women (19,20). It has been suggested that LS women have more non-endometrioid tumors compared with sporadic patients, which could at least partly explain certain of the differences in the reported risk factor profiles (19)(20)(21). LS mutation carriers in the present study used hormonal contraceptives more frequently than non-carriers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Dashti SG et al found that 7.5% of endometrial cancer patients had normal BMI 2 years before diagnosis compared to 29.6% among the control group. 18 They reported that overweight was reported in 1.5% and obese in 6.8% of the endometrial cancer patients.…”
Section: Discussionmentioning
confidence: 97%